1992
DOI: 10.1029/91ja02428
|View full text |Cite
|
Sign up to set email alerts
|

Observations from Millstone Hill during the geomagnetic disturbances of March and April 1990

Abstract: The incoherent scatter radars at Millstone Hill operated continuously during the periods March 16–23 and April 6–12, 1990, providing observations of large‐scale ionospheric structure and dynamics over a large portion of eastern North America. Major geomagnetic storms occurred during each of these periods, with deep nighttime ionospheric troughs and large magnetospheric convection electric fields observed equatorward of Millstone. The Millstone observations provide a comprehensive data set detailing storm‐induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 41 publications
(17 reference statements)
4
88
0
Order By: Relevance
“…The location of Millstone Hill is such that significant ionospheric structure falls well within the radar's field of view. The ionospheric total density trough is observed nearly overhead at Millstone Hill almost every night, and the equatorward offset of the north geomagnetic pole nearly along the Millstone Hill meridian brings high-latitude and auroral phenomena into the observatory's near field of view during geomagnetic storms [e.g., Buonsanto et al, 1992]. During disturbed conditions, intense convection electric fields occur at previously subauroral latitudes, resulting in the formation of a deep, narrow F region ionization trough.…”
Section: Storm-enhanced Densitymentioning
confidence: 99%
“…The location of Millstone Hill is such that significant ionospheric structure falls well within the radar's field of view. The ionospheric total density trough is observed nearly overhead at Millstone Hill almost every night, and the equatorward offset of the north geomagnetic pole nearly along the Millstone Hill meridian brings high-latitude and auroral phenomena into the observatory's near field of view during geomagnetic storms [e.g., Buonsanto et al, 1992]. During disturbed conditions, intense convection electric fields occur at previously subauroral latitudes, resulting in the formation of a deep, narrow F region ionization trough.…”
Section: Storm-enhanced Densitymentioning
confidence: 99%
“…Equation (1) uses n O+,O collision frequency, which, as the other ones, is taken from Banks and Kockarts [1973]. However, in some publications devoted to ISR data analyses [Burnside et al, 1987[Burnside et al, , 1988[Burnside et al, , 1991Buonsanto et al, 1989Buonsanto et al, , 1992aBuonsanto et al, , 1992b it was suggested that n O+,O collision frequency should be increased by a factor of 1.7. But later a much lower factor of 1.2-1.4 was recommended by Pesnell et al [1993], Reddy et al [1994], and Davis et al [1995].…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…6. The method of x derivation at Millstone Hill is described by Buonsanto (1990) and Buonsanto et al (1992a). The calculated x repeats Millstone Hill day-to-day x , the relative variation being more poleward on March 16, 17 and 19, coincides on March 18 and 20, but di ers in sign on March 22.…”
Section: Observations and Calculationsmentioning
confidence: 99%
“…Such an accuracy is, in principle, quite su cient for the ®rst step of solution ®nding. On the other hand, daytime electric ®elds were small for the period in question (Buonsanto et al, 1992a), so the frictional term was ignored in Eq (2 ] values, which are ®nally speci®ed at the second step using a standard multi-regressional method with physical constraints on the parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation